(untitled) (Al-Academy, 2016)
Play a movie role now is very dangerous on a large scale, in the transfer of data in a language of thought and life -strong common understanding , tools and more permeable and effectiveness in the formation of thought and conscience of recipients. Which is an instrument of culture and knowledge , and a means of effective educational tools that aim to improve the community , also plays a prominent role in shaping society’s values , and customs , and the arts , as well as used as a means of guiding , counseling and cultural enlightenment , cinema and TV gives the viewer the ability to move from one place to another by the watch and compare it to what it is , which raises the desire to improve the level , where nearly movie scenes in various other ways of life . It has become a cinema nowadays splash force to be reckoned with , have been accompanied by scientific and technical progress in human societies .It provides the basics that have become a vital part of the life of cultured human has launched a researcher from the principle of recognition and look at the experiences of the creators of the various nationalities in the jurisdiction to be of help to us in establishing the rules of aesthetic and technical fit with what we aspire to in the upgrading process artistic creativity in the new Iraq and deeper insights into the experiences of the creators of them in this research will address the researcher experience film has been characterized Ntegath excellence in terms of intellectual , aesthetic and creative in the field of filmmaking spanning more than twenty years of Spanish director Pedro Almodovar to respond to document and study the experience of the creator is not the process easy as it seems to get tender Finished this artist diversified in the field of cinema , so it may felt researcher is seen through and see the creations of art in the field of output and that touches study an important aspect characterized the director’s not an element irony that characterized an important part of its business and in light of the availability of the researcher of sources this will be accomplished scientific research for narrative irony in the films of Pedro Almodovar, the Spanish director